Antimicrobial Peptides SET-M33L and SET-M33L-PEG Are Promising Agents Against Strong Biofilm-Forming P. aeruginosa, Including Multidrug-Resistant Isolates - Alessio Fontanot; Peter D. Croughs; Clelia Cortese; Adrianus C. J. M. de Bruijn; Chiara Falciani; Alessandro Pini; Isabella Ellinger; Wendy W. J. Unger; John P. Hays (Antibiotics, 2025)
Background: The antimicrobial peptides (AMPs) SET-M33L and SET-M33L-PEG were investigated against 10 clinical isolates of P. aeruginosa. Methods: Their minimum inhibitory concentrations (MICs), minimum bactericidal concentrations (MBCs), and minimum biofilm inhibitory concentrations (MBICs) were evaluated against tobramycin, ceftazidime, and polymyxin B. Results: MICs and MBCs were 7- to 100-fold lower than tobramycin, and 10- to 300-fold lower than ceftazidime. Fractional inhibitory concentration (FIC) indices showed an additive effect, while fractional bactericidal concentration (FBC) indices showed synergistic effects (FBC < 0.5) for most isolates. Conclusion: SET-M33L and SET-M33L-PEG are promising antimicrobial agents against strong biofilm-forming P. aeruginosa, including MDR isolates.